Bee species (Hymenoptera: Anthophila) in a Cerrado-Atlantic Forest ecotone: nesting habits related to foraging activity in a degraded forest fragment - Polatto, Leandro Pereira; Alves Junior, Valter Vieira (EntomoBrasilis, 2020)
The aim of this paper was to determine the species diversity and frequency of foraging performed by bees in fragment of degraded forest in a Cerrado-Atlantic Forest ecotone area, also considering the nesting habit of each species. The foraging frequency of each bee species in the main floral sources was recorded for 12 consecutive months. The nesting site was used to sort the bees into guilds: above-ground nesting bees, ground-nesting bees, and both below and above-ground nesting bees. The guild of ground-nesting bees had 24 species and accounted for 17.48 % of the foraging rate, while above-ground nesting bees were represented by 12 species which made 8.89 % of the foraging rate, and both below and above-ground nesting bees comprised five species which made 0.43 % of the foraging rate. Africanized honeybee performed 73.20 % of the foraging flight, and presented a broad food niche. Therefore, in the forest fragment studied, two types of impacts which make difficult the survival and maintenance of the native bee fauna were observed: the dominance over floral resources by the exotic species the Africanized honeybees; the small number of large trees.